Identification of Hardware and Software Used by The Teacher in The English Classroom at Private Junior High School in North Bali - Wijaya, Kadek Ade Prihatma (Journal of Educational Study, 2024)
The rapid integration of Information and Communication Technology (ICT) in education has transformed English language teaching, but its application in resource-limited settings such as private junior high schools in Buleleng, North Bali, remains underexplored. This qualitative descriptive study identified the types of hardware and software used by English language teachers in six private junior high schools and examined their roles in preparation, implementation, and evaluation. Data were collected through questionnaires and classroom observations, following Miles and Huberman’s qualitative analysis framework. The study findings revealed that teachers utilize hardware, including laptops, smartphones, LCD projectors, internet connections, and audio amplifiers, as well as software, such as Microsoft PowerPoint, Microsoft Word, Online Dictionary, Canva, YouTube, Quizizz, and Kahoot, to enhance lesson delivery and student engagement. These devices support interactive learning, particularly in vocabulary and speaking skills, but their use varies, with some teachers not fully utilizing the software for assessment. Challenges such as unreliable Wi-Fi and limited teacher training hinder effective ICT integration. This study highlights the potential of ICT to create dynamic English classrooms while highlighting the need for infrastructure improvements and professional development. The findings offer practical insights for educators and policymakers to optimize the use of ICT in similar educational contexts.